Does 68Ga-DOTA-NOC-PET/CT impact staging and therapeutic decision making in pulmonary carcinoid tumors?. Issue 10 (October 2020) - Purandare, Nilendu C.; Puranik, Ameya; Agrawal, Archi; Shah, Sneha; Kumar, Rajiv; Jiwnani, Sabita; Karimundackal, George; Pramesh, C.S.; Rangarajan, Venkatesh
Abstract : Objective: Purpose of this study was to assess the utility of 68 Ga-DOTA-NOC-PET/computed tomography (CT) (Ga-NOC-PET) in tumor detection, pathological differentiation and baseline staging of pulmonary carcinoids as well as to study its impact on therapeutic decision making. Patients and methods: Patients who underwent a Ga-NOC-PET for initial evaluation of bronchopulmonary carcinoid tumors from August 2014 to December 2019 were included. Detection rate of Ga-NOC-PET for the primary lesion was calculated by visual estimation of tracer uptake as per Krenning score. SUVmax of typical and atypical carcinoid tumors was measured and difference compared using nonparametric statistical tests. Proportion of patients with distant metastases was also calculated and its impact on intended treatment was assessed. Results: Imaging, histopathology and treatment details of 119 patients were available for analysis. Majority of tumors had an endobronchial location (74.7%) and showed histopathologic features of typical carcinoid (82.3%). Ga-NOC-PET showed a detection rate/sensitivity of 92.4%. Oncocytic variant on histopathology and smaller tumor size accounted for majority of negative results. Typical carcinoids showed significantly higher SUVmax than atypical tumors (median SUVmax 38.4 vs. 15.7, P  = 0.002). Metastases to distant sites outside the thorax were seen in 14 patients (11.7%), primarily in liver and bones changing the intent of treatment from surgery to systemic therapy. Conclusion: Ga-NOC-PET detects asymptomatic distant metastatic disease in a sizeable number of patients (11.7%) with pulmonary carcinoid and thus contribute to clinical management by precluding futile surgeries. It shows a high sensitivity for tumor detection and can help differentiate between typical and atypical carcinoid variants by virtue of their variable tracer uptake. PET/CT using Ga-labeled DOTA peptides should be an integral part of diagnostic workup of patients with lung carcinoid.